High speed rail transport valuation - Pimentel, Pedro (2008)
The present paper investigates the optimal timing of investment for a high speed rail (HSR) project, in an uncertain environment, using a real options analysis (ROA) framework. It develops a continuous time framework with stochastic demand that allows for the determination of the optimal timing of investment and the value of the option to defer in the overall valuation of the project. The modelling approach used is based on the differential utility provided to railway users by the HSR service.